Ventromedial prefrontal volume in adolescence predicts hyperactive/inattentive symptoms in adulthood - Albaugh, Matthew; Banaschewski, Tobias; Flor, Herta; Grimmer, Yvonne; Nees, Frauke; Poustka, Luise; Struve, Maren (Cerebral cortex, 2019)
Abstract: Youths with attention-deficit/hyperactivity disorder symptomatology often exhibit residual inattention and/or hyperactivity in adulthood